Avaliação toxicológica do biofertilizante Beifort® em Drosophila melanogaster: análise comportamental, citotóxica e genotóxica - Rieder, Guilherme Schmitt (2024)
The continued growth of the human population around the world has required an increase in food production. To meet these nutritional needs, the use of fertilizers has become an indispensable input in agriculture, contributing to major improvements in food production. The application of fertilizers and pesticides also causes several environmental impact effects. The growing and indiscriminate consumption of chemical fertilizers is increasingly contributing to water pollution, an increase in atmospheric ammonia, methane and carbon dioxide in global emissions due to the dispersion of the use of minerals and thus damaging the environment. To maintain high crop productivity without harming the ecosystem, biofertilizers have emerged as an alternative to reduce the use of chemical fertilizers. Thus, environmentally safer biofertilizers can replace the exploitation of more toxic chemical fertilizers. In this context, the fly D. melanogaster was used to study the potential toxicity of the biofertilizer Beifort®. The flies were exposed to high concentrations of Beifort® in the diet (1.8 mL/L, 9.0 mL/L and 18 mL/L), and the morphological and behavioral toxic effects were analyzed (egg development to adulthood, longevity of flies, climbing performance, memory and associative learning, damage to the digestive tract of larvae and breakage of plasmid DNA). Beifort® did not promote changes in the flies' development, survival, locomotor activity or memory. It did not cause damage to digestive tract cells, and did not induce DNA breakage in vitro. Thus, it did not cause toxicity to D. melanogaster after in vivo exposure. Therefore, in addition to promoting the sustainable use of agricultural waste, the use of Beifort® can contribute to reducing the use of chemical fertilizers and thus help reduce the environmental impacts caused by them on the nvironment.